Pendampingan Pencegahan Stunting Berbasis Tata Kelola Akuntansi Rumah Tangga di Desa Bakung Kabupaten Serang - Arianto, Bambang; Handayani, Bekti (Rahmatan Lil 'Alamin Journal of Community Services, 2023)
Stunting prevention program has become a national health program that has been started in a structured way from the central level to rural areas. Efforts to prevent stunting, especially in rural areas, are still hampered due to the lack of knowledge and understanding in household accounting management. The impact is that the mothers of toddlers are not able to meet the nutrition of toddlers properly due to poor household financial management. In the community service activity in Bakung Village, Serang Regency on 22th January 2023, assistance was provided on stunting prevention strategies based on the strengthening of household accounting governance. In this assistance, a variety of new knowledge and technical assistance has been given regarding efforts to prevent stunting based on household accounting according to the character of the rural community. The success of this service activity is seen from the beginning to increase the knowledge and understanding of the mothers of toddlers about the importance of household accounting in the management of nutritious food for the prevention of stunting. The final result of the activity is that the strengthening of household accounting governance can provide new knowledge and technical understanding for mothers under five in the prevention strategy of stunting in Bakung Village, Serang Regency.